Анализ критических режимов систем с динамической защитой от вредных воздействий - Попсуев, М. С.; Наумейко, И. В.; Сова, А. В. (ХНУРЭ, 2015)
The model of dynamic system describing the situation when the main subsystem "produces" a detrimental factor, and the second subsystem, "defense", tries to reduce it completely, or at a reasonable price.
Keywords: динамическая защита; критический режим